Effect of SARS-CoV-2 infection in neonates or in pregnancy on developmental outcomes at 21-24 months (SINEPOST): study protocol for a prospective cohort study - Samantha Johnson; Ela Chakkarapani; Jenny Kurinczuk; Rosie P Cornish; Kathryn Woodward (BMJ Publishing Group, 2022)
Introduction Exposure to SARS-CoV-2 during pregnancy or in the neonatal period may impact fetal or neonatal brain development either through direct central nervous system infection or indirectly through the adverse effects of viral infection-related inflammation in the mother or newborn infant. This study aims to determine whether there are early neurodevelopmental effects of SARS-CoV-2 infection.Methods and analysis We will conduct a prospective national population-based cohort study of children aged 21-24 months who were born at term (≥37 weeks' gestation) between 1 March 2020 and 28 February 2021 and were either antenatally exposed, neonatally exposed or unexposed (comparison cohort) to SARS-CoV-2. Nationally, hospitals will identify and approach parents of children eligible for inclusion in the antenatally and neonatally exposed cohorts using information from the UK Obstetric Surveillance System (UKOSS) and British Paediatric Surveillance Unit (BPSU) national surveillance studies and will identify and approach eligible children for the comparison cohort through routine birth records. Parents will be asked to complete questionnaires to assess their child's development at 21-24 months of age. Outcome measures comprise the Ages and Stages Questionnaire, Third Edition (ASQ-3), Ages and Stages Questionnaire Social-Emotional, Second Edition (ASQ-SE-2), Liverpool respiratory symptoms questionnaire and questionnaire items to elicit information about healthcare usage. With parental consent, study data will be linked to routine health and education records for future follow-up. Regression models will compare ASQ-3 and ASQ-SE-2 scores and proportions, frequency of respiratory symptoms and healthcare usage between the exposed and comparison cohorts, adjusting for potential confounders.Ethics and dissemination Ethics approval was obtained from the London-Westminster Research Ethics Committee. Findings will be disseminated in scientific conference presentations and peer-reviewed publications.ISRCTN registration number ISRCTN99910769.